ANALYSIS OF INTERNATIONAL EXPERIENCE: CRITICAL THINKING APPROACHES IN FOREIGN LANGUAGE TEACHER TRAINING (SCIENCE TIME JOURNAL, 2026)
This article presents a systematic comparative analysis of international approaches to developing critical thinking competencies in prospective foreign language (EFL/ESL) teachers within the framework of digital and competency-based education. Drawing on empirical and theoretical studies published between 2018 and 2024, the research examines pedagogical models adopted in Finland, the United States, South Korea, Australia, and Estonia — five countries consistently recognised as leaders in educational innovation. The article employs a mixed-method analytical framework combining documentary analysis, content analysis of peer-reviewed literature, and comparative pedagogical synthesis. Findings reveal that effective critical thinking integration in EFL teacher preparation programmes requires a convergence of inquiry-based learning, reflective practice, collaborative dialogue, and technology-enhanced instruction. Implications are drawn for reforming teacher education curricula in Central Asian contexts, particularly Uzbekistan, in alignment with national educational modernisation goals.